Analisis Kesulitan Belajar Bahasa Indonesia Materi Menentukan Ide Pokok dan Ide Pendukung Pada Siswa Kelas IV Sekolah Dasar - Damaiyanti, Rosi; Mardiana, Dina; Dilla, Widya Permata (Jurnal Pendidikan Dasar dan Menengah, 2024)
Determining the main idea and supporting ideas of a text is a fundamental reading skill. The ability of students to identify the main idea and supporting details is a key aspect of Indonesian language learning in fourth grade. However, at SDN-11 Palangka, many fourth-grade students—approximately 73%—struggle with identifying the main idea and supporting ideas. Despite being an upper-grade class, these students should be capable of applying reading comprehension skills effectively. This has led researchers to conduct descriptive research aimed at identifying the difficulties, causal factors, and potential solutions to improve the learning of Indonesian. The focus of this study is on determining the main idea in reading texts for fourth-grade students at SDN-11 Palangka. The research employs a descriptive method with a qualitative approach, utilizing an interactive data analysis technique based on the Miles and Huberman model. This process involves data collection, data reduction, data presentation, and conclusion drawing. The data collection methods used in this research include observation, interviews, and documentation. The results indicate that the main difficulty students face in identifying the main idea is their inadequate understanding of the material related to the main idea and supporting details. The cause of these difficulties lies in the students' reading challenges, which include a lack of fluency in reading and insufficient reading comprehension skills.